Microscopy‐guided laser ablation for the creation of complex skin models with folliculoid appendages - Carla M. Abreu; Luca Gasperini; Manuela E. L. Lago; Rui L. Reis; Alexandra P. Marques (Wiley, 2021)
Abstract Engineering complex tissues requires the use of advanced biofabrication techniques that allow the replication of the tissue's 3D microenvironment, architecture and cellular interactions. In the case of skin, the most successful strategies to introduce the complexity of hair follicle (HF) appendages have highlighted the importance of facilitating direct interaction between dermal papilla (DP) cells and keratinocytes (KCs) in organotypic skin models. In this work, we took advantage of microscopy‐guided laser ablation (MGLA) to microfabricate a fibroblast‐populated collagen hydrogel and create a subcompartment that guides the migration of KCs and lead their interaction with DP cells to recreate follicular structures. Upon definition of the processing parameters (laser incidence area and power), MGLA was used to create 3D microchannels from the surface of a standard organotypic human skin model up to the aggregates containing DP cells and KCs, previously incorporated into the dermal‐like fibroblast‐collagen layer. Analysis of the constructs showed that the fabricated microfeatures successfully guided the fusion between epidermal and aggregates keratinocytes, which differentiated into follicular‐like structures within the organotypic human skin model, increasing its functionality. In summary, we demonstrate the fabrication of a highly structured 3D hydrogel‐based construct using MGLA to attain a complex skin model bearing folliculoid structures, highlighting its potential use as an in vitro platform to study the mechanisms controlling HF development or for the screening of bioactive substances.